Retelling trickster in Naapi's language - Howe, Nimachia, author; Utah State University Press, publisher (Colorado State University. Libraries, 2019)
An examination of Niitsitapisinii (Blackfoot) origin stories about one of the powerful and unpredictable creators in Niitsitapii consciousness: Naapi. Through in-depth linguistic analysis, Howe reinterprets the earliest references to Naapi, offering an authentic understanding of his identity and the meanings and functions of the stories he appears.--Provided by publisher.
1. Who is Naapi? Sign as First Language -- 2. Naapi's Name -- 3. Myth, Legend, and Naapi -- 4. A Different Conceptual Order -- Appendix: Selected Naapi Stories; Person's Face; Lone Woman; Lone Pine; Wheel Game; Sliding Place.
Keywords: Naapi -- (Trickster); Siksika language; Indians of North America -- Folklore; Siksika Indians -- Folklore